A Generalized Equivalence Method for the Calculation of Low-Frequency EMI on Pipeline Networks Considering Polarization Effect - Liu, Min-zhou; Xie, Yan-zhao; Wu, Yu-ying; Trinchero, Riccardo; Stievano, Igor Simone (IEEE transactions on power delivery, 2024)
Large-scale pipeline networks may be subject to wide-area and spatially nonuniform external electromagnetic interference. This paper presents a generalized and efficient algorithm for the calculation of inductive and conductive coupling to pipeline networks based on the two-port equivalent circuit. In the modified transmission line model of the pipeline, the external inteference are characterized by using only longitudinal voltage sources. In addition, the nonlinear polarization of coating breakdown is incorporated into the circuit model of the network. The linear pipe segments can be independently reduced to the equivalent-pi circuit with analytical parameters, which enables model order reduction of the network. Such techniques can be applied to arbitrary nonuniform excitation fields. Several test cases are used to illustrate the response characteristics of pipelines excited by interference with different spatial patterns, including geomagnetic disturbances and HVDC earth return currents.